2006
DOI: 10.1063/1.2345239
|View full text |Cite
|
Sign up to set email alerts
|

Hole-transporting interlayers for improving the device lifetime in the polymer light-emitting diodes

Abstract: The authors report the effect of thermal treatment of hole-transporting interlayers between a polymeric hole injection layer and an emitting layer (EML) on the luminous efficiency and the lifetime performance in blue polymer light-emitting diodes. As the thermal annealing temperature of the interlayer increased, the hole mobility of the interlayer tended to decrease, which results in reducing the hole current injected into the EML in the devices. Hence, the device luminous efficiency decreased due to lower ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 14 publications
3
26
1
Order By: Relevance
“…Recently, several groups reported use of thin interfacial layers on top of PEDOT:PSS layer which enhances hole injection, electron-blocking, and device lifetime. [21][22][23] We speculate that our surface layer may have similar roles with the interfacial layers. The detailed lifetime-enhancing mechanism can be another research topic.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several groups reported use of thin interfacial layers on top of PEDOT:PSS layer which enhances hole injection, electron-blocking, and device lifetime. [21][22][23] We speculate that our surface layer may have similar roles with the interfacial layers. The detailed lifetime-enhancing mechanism can be another research topic.…”
Section: Resultsmentioning
confidence: 99%
“…The high-energy gap essential for deep blue light emitting polymer often results in low electron affinities, which hampers the electron injection and the balance of the charge carriers [14,15]. To solve the problem, multilayered structure which constitutes an electron transport layer, an emitting layer and a hole transport layer are widely applied to improve the performance of the devices [16][17][18][19][20][21]. But the sequential deposition of these layers provides additional complexity and the cost of such devices will be increased.…”
Section: Introductionmentioning
confidence: 98%
“…phenylenediamine) (PFB) and poly(N-vinylcarbazole) (PVK), finding that while luminous efficiencies could be improved, baking the interlayers at elevated temperatures decreased the efficiency but increased the device lifetime. [9] In the PFB devices, this involved nearly a three-fold lifetime improvement. Zacharias et al demonstrated high-efficiency (19.2 cd A À1 ) blue phosphorescent organic LEDs (OLEDs) using 8 nm interlayers of an oxetanefunctionalized, cross-linkable hole transport material.…”
Section: Introductionmentioning
confidence: 99%